Anisotropic Ballistic Transport through a Potential Barrier on Monolayer Phosphorene*Supported by the National Natural Science Foundation of China under Grant No 11374002, the Hunan Provincial Natural Science Foundation of China under Grant No 13JJ2026, the Scientific Research Fund of Hunan Provincial Education Department under Grant No 12B010, the Science and Technology Innovative Research Team in Higher Educational Institutions of Hunan Province, and the Construct Program of the Key Discipline in Hunan Province. (May 2016) - Cheng 程, Fang 芳; He 何, Bing 兵
Abstract : We demonstrate theoretically the anisotropic quantum transport of electrons through a single barrier on monolayer phosphorene. Using an effectivek·p Hamiltonian, we find that the transmission probability for transport through n–n–n (or n–p–n) junction is an oscillating function of the incident angle, the barrier height, as well as the incident energy of electrons. The conductance in such systems depends sensitively on the transport direction due to the anisotropic effective mass. By tuning the Fermi energy and gate voltage, the channels can be transited from opaque to transparent, which provides us with an efficient way to control the transport of monolayer phosphorene-based microstructures.